Micropropagation of endangered slipper orchid, Paphiopedilum rothschildianum (Rchb. F) stein - Ng, Chyuam Yih (2011)
Paphiopedilum rothschildianum, a highly endangered slipper orchid species endemic to Mount Kinabalu, Sabah, Malaysia, is strictly protected under Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). A study was carried out to establish in vitro culture system and to develop efficient propagation strategies to prevent this species from being extinct. The effect of casein hydrolysate, peptone and tryptone peptone at concentrations of 0.5, 1.0 and 2.0 g/L on multiple shoots induction of P. rothschildianum were studied. Additions of 1.0 g/L peptone into PGR-free ½ MS has resulted in the formation of 2.9 shoots per nodal stem explants; whereas, 2.8 shoots were produced from a single shoot after 16 week of culture on PGR-free ½ MS supplemented with 2.0 g/L tryptone-peptone. The study was also conducted to investigate the effects of cytokinins, organic additives and combination of cytokinin and organic additives on multiple shoot formation of P. rothschildianum. The additions of 4 μM BAP together with 2 g/L peptone and 60 g/L potato homogenate in ½ MS had markedly increased the number of multiple shoot formed with an average of 8.8 shoots per nodal stem explant after 12 weeks of culture. The effects of other organic additives such as banana homogenate, potato homogenate, tomato homogenate and coconut water were also evaluated on the in vitro growth and development of P. rothschildianum plantlets. Among these organic additives, addition of potato homogenate had effectively promoted the formation of new shoots (3.1 shoots per plantlet) and leaves (1.8 leaves per plantlet); and addition of tomato homogenate has shown to promote roots formation (6.2 roots per explant) in P. rothschildianum plantlets. On the other hand, the presence of coconut water was inhibitory to the proliferation of P. rothschildianum plantlets. Well developed plantlets with four to five leaves and roots were acclimatized and transferred to a glasshouse with 90% survival rate. Propagation of P. rothschildianum through formation of protocorm-like body (PLB) was also established. Secondary PLBs were successfully induced from primary PLBs which obtained from stem derived-callus, after 8 weeks of culture on ½ MS supplemented with 4μM kinetin with an average of 4.1 PLBs formed per explant. Subsequent subculture of the secondary PLBs onto PGR-free ½ MS containing 60 g/L banana homogenate for an additional 8 weeks has resulted in the three fold increased in the number of new PLBs (tertiary PLB) formation. Approximately 70% of these newly formed PLBs were regenerated into complete plantlets after 8 weeks of culture on PGR-free ½ MS containing 20% (v/v) coconut water. The outcomes of this study were suitable for in vitro conservation of this highly endangered species and could also be applied for large-scale production of this fabulous slipper orchid toward meeting the increasing demand of ornamental industry.